THE CONTENT OF SHADOWING IN PERSPECTIVE IS LIGHT AND THEIR CONDITIONS - Rahimjonova Dilfuza (Journals Park Publishing, 2023)
In this article, the essence and meaning of making a shadow in perspective depends on the factors of making it and the accuracy of the information about the structure and size of the object. If there was only light and no shadow, or only darkness (darkness) and no light, it would not be possible to see and imagine anything with the naked eye. In fine arts, artists attach great importance to the direction of light and the strength of light. For example, when painting an angry person, if the light is directed from the part below the jaw, the psychological state intended by the work will be effectively revealed. A correctly constructed perspective of an object provides information about its structure. However, in his perspective painting, it has been said that judicious use of light and shadow significantly increases the object's clarity.
Keywords: Light, body surface, Artificial lighting, Natural lighting, Shading